Answer:
13) x=4, y=0
15) x= -3, y=1
Explanation:
13. Label the 2 equations.
y= x-4 -----(1)
-4x -6y= -16 -----(2)
From (2): -2x -3y= -8 -----(3)
(divide by 2 throughout)
Subst. (1) into (3):
-2x -3(x-4)= -8
-2x -3x +12= -8 (expand)
-5x= -8 -12 (simplify, constant to 1 side)
-5x= -20 (simplify)
x= 4 (divide by -5 throughout)
subst. x=4 into (1):
y= 4 -4
y= 0
15. x= y -4 -----(1)
-2x +3y= 6 -----(2)
subst. (1) into (2):
-2(y-4) +3y= 6
-2(y) -2(-4)= 6 (expand)
-2y +8= 6
-2y= 6 -8 (bring constant to 1 side)
-2y= -2
y= 1 (divide by -2 throughout)
subst. y=1 into (1):
x= 1 -4
x= -3